PERTUMBUHAN EKONOMI DAN INFLASI DAERAH: STUDI KASUS DATA PANEL DI INDONESIA (Jurnal Bakti Masyarakat Indonesia, 2019)
This study aims to analyze the macroeconomic factors that affect economic growth and regional inflation. It also analyzes the role of the Regional Inflation Control Team (TPID) in controlling regional inflation. Data used in this research include macro data from 33 provinces in Indonesia year 2004-2014. Model Analysis that employed in this research is Simultaneous Panel Equation to test the relationship between economic growth and regional inflation. The results of the analysis show that macro variables include Credit (Kre), Gross Fixed Capital Formation (PMTB), Labor Force Participation (LFPR) and Government Spend (Spend) effect on Economic growth. The result of inflation model showing negative or decreasing inflation chance is Human Development Index (HDI) variable, while for variable which show positive or rising inflation opportunity is Population variable (POP) and Predicted Economic growth (PDRBH). The role of TPID, among others through daily price monitoring and data collection of food stocks and moral appeal to the community to be able to address the development of prices already running, but still need to be improved